2007
DOI: 10.1001/archinte.167.8.781
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Burden Index to Define the Functional Burden of Medications in Older People

Abstract: Background: Older people carry a high burden of illness for which medications are indicated, along with increased risk of adverse drug reactions. We developed an index to determine drug burden based on pharmacologic principles. We evaluated the relationship of this index to physical and cognitive performance apart from disease indication. Methods: Data from the Health, Aging, and Body Composition Study on 3075 well-functioning communitydwelling persons aged 70 to 79 years were analyzed by multiple linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
687
2
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 604 publications
(715 citation statements)
references
References 43 publications
(24 reference statements)
13
687
2
13
Order By: Relevance
“…The DBI was developed to measure the functional burden of medications [10,11] and the EQ-5D-5L captures physical function (mobility, self-care and usual activities) while the DEMQOL does not. A previous cross-sectional study also found an association between DBI and lower health-related quality of life in older adults with dementia living in residential settings, but did not find an association with PIMs according to the Beers Criteria [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DBI was developed to measure the functional burden of medications [10,11] and the EQ-5D-5L captures physical function (mobility, self-care and usual activities) while the DEMQOL does not. A previous cross-sectional study also found an association between DBI and lower health-related quality of life in older adults with dementia living in residential settings, but did not find an association with PIMs according to the Beers Criteria [21].…”
Section: Discussionmentioning
confidence: 99%
“…DBI exposure for all resident records was calculated as the sum of exposure to each anticholinergic or sedative medication using the equation below [10]:…”
Section: Drug Burden Index and Potentially Inappropriate Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Örneğin Antikolinerjik Risk Skalası (Anticholinergic Risk Scale, ARS), İlaç Yük İndeksi (Drug Burden Index, DBI), Reçete Optimizasyon Yöntemi (Prescribing Optimization Method) bu amaçla kullanılan yöntemlerdir (35)(36)(37).…”
Section: Priscus Listesi (Potentially Inappropiate Medications In Theunclassified
“…The Screening Tool for Older Persons' Prescriptions (STOPP) and the Screening Tool to Alert Right Treatment (START) criteria have been developed and validated for European countries with results that indicate they are more sensitive to detecting ADE and prescription errors than the Beers' criteria [O'Mahony et al 2010;Delgado Silveira et al 2009;Lang et al 2009;Ryan et al 2009;Gallagher et al 2008;Topinkova et al 2008]. The Drug Burden Index (DBI) is another risk assessment tool that identifies high-risk medicines by pharmacologic class (anticholinergic and sedative) and calculates an individual's cumulative exposure to these medicines, considering both the number and dose of these medicines [Hilmer et al 2007a]. The recently developed Anticholinergic Risk Scale (ARS) is a cumulative scale that gives weight to anticholinergic medications on a three-point scale (0, no or low risk, to 3, high anticholinergic potential).…”
Section: Risk Assessment Toolsmentioning
confidence: 99%